HISAB FALAK DAN RUKYAT HILAL: ANTARA MISI ILMIAH DAN SERUAN TA’ABBUD - Shofiyullah Mukhlas (Jurnal Hukum Islam, 2009)
Hisab (calculation of reckoning) and ru'yah (determining date by sighting of moon), as the methods used to determine the beginning of Islamic calender represent two significant matters need deeper discussion. However, the different methods in the determination of lunar months system requires further discussion concerns with the validity of the methods of determining the beginning of the month, so does the method used by Rasulullah SAW. In determining the lunar months system, Hisab seems to be an attempt that uses scientific approach, while Ru'yah seems to be an attempt that use ta'abbudiyah approach. This fact is often exposes people to two alternatives, giving priority to scientific method or deemed contrary to leave the scientific method with emphasis to ta'abbudiyyah.